A Case Study of the Largest 3D Printed Villa: Breaking Boundaries in Sustainable Construction - Alqaryouti Yousef; Al Suwaidi Mariam; AlKhuwaildi Raed Mohmood; Kolthoum Hind; Youssef Issa; Al Imam Mohammed (E3S Web of Conferences)
This research paper showcases a detailed case study of the largest 3D printed villa, an architectural wonder completed on December 7, 2023, in Dubai, UAE. The project was a collaboration between Mohammed Bin Rashid Housing Establishment and 3DXB GROUP, and it set a new Guinness World Record. This groundbreaking achievement marks a new era in sustainable construction and 3D printing technology. The paper delves into the intricate process of designing and constructing the villa, highlighting innovative techniques and materials used. It also showcases the collaborative efforts of Mohammed Bin Rashid Housing Establishment and 3DXB, demonstrating their crucial support and partnership in achieving this feat. The study provides a thorough analysis of the technical aspects of 3D printing used in the villa, including material properties, design considerations, and the logistical challenges overcome during construction. Additionally, it reflects on the project’s implications for the future of the construction industry. The successful completion of the world’s largest 3D printed villa is not only a milestone for Mohammed Bin Rashid Housing Establishment but also a beacon of innovation that could inspire further advancements in sustainable construction practices worldwide. The study concludes by emphasizing the need for continued research and development in 3D printing technology to further its application in large-scale construction projects.